A crowdsensing cloud-based microservice for weather forecast - Selis, Dimitris; Papaioannou, Evi; Moisiadis, Giorgos; Kaklamanis, Christos (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
We present a cloud-based microservice enabling individual users to have access to local air pressure measurements and a proof-of-concept web application providing shot-term weather forecasts based only on local crowdsensed data. Our microservice has been developed using state-of-the-art web technologies and cutting-edge technologies related to cloud computing. Apart from its individual interest and potential usefulness, our microservice and proof-of-concept web application show how modern cloud-based technologies and tools can be nicely combined to improve the community daily routine and wellbeing.